Global shifts in osteoarthritis subtype trends among older adults due to elevated BMI: an age-period-cohort analysis based on the global burden of disease database - Zhiqiang Li; Yaxiang Chen; Zhao Shen (Frontiers in Public Health)
PurposeIt remains unclear whether elevated Body Mass Index(BMI)has a similar impact on the disease burden of osteoarthritis subtypes in older adults. This study aims to compare the long-term trends of osteoarthritis subtypes caused by high BMI across different gender groups globally from 1990 to 2021.MethodsWe obtained cross-sectional data from the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2021 (https://vizhub.healthdata.org/gbd-results/). The disease burden of osteoarthritis subtypes in older adults attributable to high BMI was quantified using Years Lived with Disability (YLDs). Linear regression and the Age-Period-Cohort (APC) method were employed to calculate the trends in Age-standardized Years lived with disability rate (ASYR), adjusting for age, period, and cohort effects.ResultsThe ASYR of osteoarthritis attributable to high BMI in older adults globally has shown a continuous upward trend over the past 32 years, with an Estimated Average Percentage Change (EAPC) of 0.96 (95% CI: 0.94 to 0.99). Specifically, the EAPC for hip osteoarthritis was 0.73 (95% CI: 0.70 to 0.76), while for knee osteoarthritis, it was 0.99 (95% CI: 0.96 to 1.02). China recorded the highest number of osteoarthritis YLDs globally, reaching 0.59 million (95% UI: −0.05 to 1.71). The United States had one of the highest ASYR rates for osteoarthritis at 410.85 per 100,000 (95% UI: −44.47 to 1,083.52), while India exhibited the highest EAPC for osteoarthritis worldwide at 2.74 (95% CI: 2.70 to 2.79), with hip osteoarthritis at 3.36 (95% CI: 3.25 to 3.48) and knee osteoarthritis at 2.70 (95% CI: 2.65 to 2.75). The local drift curves indicated a slow upward trend in the annual percentage change of YLDs for both hip and knee osteoarthritis attributable to high BMI across all age groups. In terms of gender, males exhibited a higher rate and risk of YLDs associated with high BMI.ConclusionOur findings provide strong evidence that the ASYR associated with high BMI globally have continuously increased over the past 32 years, with consistent patterns of change observed across different osteoarthritis subtypes. This highlights the critical role of BMI control in effectively alleviating the burden of osteoarthritis in older adults.